Nodal involvement at nephrectomy is associated with worse survival: A stage‐for‐stage and grade‐for‐grade analysis. (8th October 2012) - Sun, Maxine; Bianchi, Marco; Hansen, Jens; Abdollah, Firas; Trinh, Quoc‐Dien; Lughezzani, Giovanni; Shariat, Shahrokh F; Montorsi, Francesco; Perrotte, Paul; Karakiewicz, Pierre I
Abstract : Objectives: To examine cancer‐specific mortality in patients with nodal metastases relative to patients without nodal involvement at nephrectomy for non‐metastatic renal cell carcinoma in a population‐based cohort. Methods: A total of 11 374 non‐metastatic renal cell carcinoma patients who underwent a lymph node dissection at nephrectomy were identified using the Surveillance, Epidemiology and End Results database (1988–2008). The 5‐year cancer‐specific mortality‐free survival rates were examined according to the presence or absence of nodal involvement within the entire cohort, and stratified according to pathological tumor stage (pT1  vs  pT2  vs  pT3  vs  pT4) and Fuhrman grade (I  vs  II  vs  III  vs  IV). Cox regression analyses for prediction of cancer‐specific mortality were modeled to assess the effect of nodal metastases versus no nodal involvement in the entire population. Finally, separate Cox regression models were fitted within each pathological stage and grade. Results: Overall, 1260 (11%) patients had nodal metastases at nephrectomy. The overall 5‐year cancer‐specific mortality‐free survival rates were 38.4 versus 83.8% in patients with nodal metastases and without nodal metastases, respectively. In multivariable analyses, amongst pT1, pT2, pT3 and pT4, patients with nodal metastases were 6.0‐, 3.6‐, 3.2‐ and 2.0‐fold, respectively, more likely to die after nephrectomy (all P  < 0.001). Similarly, amongst Fuhrman grade I, Fuhrman grade II, Fuhrman grade III and Fuhrman grade IV, patients with nodal metastases were 3.9‐, 3.5‐, 3.1‐ and 2.7‐fold, respectively, more likely to die of cancer‐specific mortality (all P  < 0.001). Conclusions: Nodal involvement is an important determinant of higher cancer‐specific mortality after nephrectomy. The detrimental effect of nodal metastases is particularly strong amongst patients with low‐stage or low‐grade non‐metastatic renal cell carcinoma.